Implementing Peer-Review to Support Business English Writing among EFL Learners - Wicaksana, GDA; Sudrajat, Kadek; Suprihatin, Yeni; Mahadipta, Ngurah Gede Dwi; Baur, Kim; Karisyati, Ni Putu; Pratama, Putu Yogi Agustia; Prasetya, Guntur Nanda; Junior, Jacinto Oliveira (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
This study examines the implementation of peer-review in developing Business English writing skills among undergraduate business students at Institut Desain dan Bisnis Bali. A mixed-method research design was employed involving 39 students enrolled in an English for Business course over one semester, with the course lecturer included as an informant. Data were collected through classroom observations, documentation of students’ writing drafts and peer-review activities, and a perception survey using a five-point Likert scale. Qualitative data were analyzed descriptively to explore the peer-review process, instructional scaffolding, and student engagement, while quantitative data were analyzed using descriptive statistics and interpreted based on Koyan’s (2012) perception criteria. The findings reveal that structured peer-review supports students’ writing development by enhancing grammatical awareness, word choice, and active classroom participation. Quantitative results indicate very high student perceptions of teacher performance, with a mean score of 4.48, reflecting strong pedagogical, cognitive, and affective competencies. Addressing a research gap, this study situates peer-review within Business English instruction in a heterogeneous EFL classroom, an area that remains underexplored. The study contributes theoretically to peer-review pedagogy and practically by proposing a structured peer-review model that facilitates active learning and writing development in Business English contexts.